Three venues to the theory of persuasion. Issue 1 (1st June 2019) - Bar-Am, Nimrod
Logic, Rhetoric and Argumentation Theory are more or less distinct attempts to approach the riddle of persuasion: what makes our reason tick? Moreover, how best can we study our ability to influence the reason of others so as to make them share our opinions? The three classical answers, then, are: (1) Logic, the theory of valid inference, is the best persuasion theory available. (2) Rhetoric, the theory of effective manipulation of others is the best persuasion theory available. Finally, (3) Argumentation theory, the middle theory that recommends a mix of reasoning and manipulation, is the best persuasion theory available. In this article, I briefly explain the controversy between these three competing views and offer some comments upon its possible resolution. Since all forms of communication are performed on the spectrum between manipulation and the non-manipulative offering of contents, this controversy should interest all those who are intrigued by the miraculous possibility of human communication in the first place.